Strategies used by teacher to get the student recognize and manage all forms of the plural of the nouns. - Sisalima Jaramillo, Damaris Johanna (Machala : Universidad Técnica de Machala, 2015)
Las estrategias son todos los procedimientos , actividades, técnicas , métodos, etc. , que utiliza el maestro con el fin de dirigir el proceso de enseñanza-aprendizaje , por lo que los estudiantes desplegaron una actividad mental constructiva rica y diversa basada en el conocimiento previo de que los estudiantes tienen la posibilidad de un desarrollo individual y social , ofreciendo a los estudiantes la oportunidad de ser directores de su aprendizaje real y significativo .
The strategies are all the procedures, activities, techniques, methods, etc., which uses the teacher in order to lead the teaching-learning process, making the students deployed a constructive mental activity rich and diverse based on the prior knowledge that students have the possibility of an individual and social development, offering students the opportunity to be directors of their real and meaningful learning.
Keywords: TEACHER; STRATEGY; PLURAL; NOUN